2013
DOI: 10.1002/marc.201300395
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Free‐Standing Polymer Brush Films Based on a Colorless Polydopamine Thin Layer

Abstract: A free-standing polymer brush film with tailored thicknesses based on a colorless polydopamine (PDA) thin layer is prepared and characterized. The surface-initiated atom transfer radical polymerization (ATRP) of 2-hydroxyethyl methacrylate (HEMA) is performed on a PDA layer with thickness of ca. 6 nm, which generated an optically transparent and colorless free-standing PHEMA brush film (1.5 cm × 1.5 cm). Because the cross-linked PDA layer is used as the base for the polymer brushes, the reported method does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 34 publications
2
40
0
Order By: Relevance
“…6a), CaCO 3 @PDA/OEGA m particles were well dispersed. showed that their color changes decreased as the m value increased, in agreement with our previous report [17]. The dark brown coloration also decreased with increasing Et 3 N concentration (Fig.…”
Section: One-step Hierarchically Structured Coatingssupporting
confidence: 92%
See 2 more Smart Citations
“…6a), CaCO 3 @PDA/OEGA m particles were well dispersed. showed that their color changes decreased as the m value increased, in agreement with our previous report [17]. The dark brown coloration also decreased with increasing Et 3 N concentration (Fig.…”
Section: One-step Hierarchically Structured Coatingssupporting
confidence: 92%
“…This phenomenon is probably due to the thin thickness of the PDA/BiBB 2 layer thickness. The thicknesses of PDA/BiBB 2 on glass plate [17] and PSt particles [18], measured by atomic force microscopy (AFM) and SEM, were determined to be ca. 6 nm and 7 nm, respectively, indicating thin thickness of PDA/BiBB 2 layer.…”
Section: Two-step Hierarchically Structured Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the strong adhesion makes it contaminate the manufacturing equipments. The deep color of PDA-coated surfaces may be also a problem in some cases [176,177]. To overcome these shortcomings, researchers are looking for the alternative choices [178].…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis, processing and characterization of such complex brush structures, for example, mixed brushes [193][194][195][196][197], multiblock copolymer brushes [114,115,198], gradient polymer brushes [199,200], nanopatterned polymer brushes [107,116], polymer carpet/Janus membrane [8,[201][202][203] and polymer nanochannels [114,117] are of great interest from a fundamental as well as technological perspective. Comprehensive understanding of structure-property relationships in well-defined and fully characterized polymer brushes aided by new synthesis as well as predictive modeling can open up newer applications for polymer brushes.…”
Section: Discussionmentioning
confidence: 99%